PENGGUNAAN POLYSTYRENE SEBAGAI BETON RINGAN DENGAN PRA PEMADATAN UNTUK PANEL DINDING TEBAL 10 CM - , Arnas Aidil ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Bricks and concrete blocks are the common wall materials with disadvantages such as heavy own weight, which adds the dead load of structure. Moreover, the impact of the use of soil as the main material reduces the productive land. One of the lightweight materials applicable for lightweight concrete is polystyrene. This material is soft and its shape is easy to change. Polystyrene can be used as filler in concrete because it provides air voids in the concrete mix. The research was carried out by using shredded polystyrene waste as one of materials of lightweight concrete under the pre-compaction method. The wall panel dimensions were 90 cm of length, 30 cm of width and 10 cm of thickness. A layer of the welded wiremesh was then given on both sides within 1 cm distance from the edge. Between the layers of the welded wiremesh, a connector in 8 cm of length was given within 10 cm distance. Variations of the mixture consisted of polystyrene concrete with no fine aggregate content and polystyrene concrete with 5% fine aggregate content. The variations of the welded wiremesh consisted of one with grid pattern in 1x1 cm size and 0.60 mm diameter, and the other with grid pattern in 2x2 cm size and 0.81 mm diameter. The results of this research show that 0.055 MPa, pre-compaction given to the polystyrene concrete cube specimen with no fine aggregate indicate compressive strength, density and modulus of elasticity of 0.860 MPa, 665.73kg/m3 and of 161.86 MPa, respectively. Whereas the polystyrene concrete with 5% fine aggregate content indicate compressive strength, density and elasticity modulus of 1.052 MPa, 716.88 kg/m3 and 175.39 MPa, respectively. Given with 0.052 MPa pre-compaction, the polystyrene concrete wall panel with no fine aggregate content show the flexural strength of 0.423 MPa. Given with 0.044 MPa pre-compaction, the polystyrene concrete wall panel with no fine aggregate content indicate compressive strength of 1.066 MPa.